2019
DOI: 10.1016/j.anifeedsci.2019.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Small differences in biohydrogenation resulted from the similar retention times of fluid in the rumen of cattle grazing wet season C3 and C4 forage species

Abstract: , Small differences in biohydrogenation resulted from the similar retention times of fluid in the rumen of cattle grazing wet season C3 and C4 forage species, Animal Feed Science and Technology (2019),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
3
0
1
Order By: Relevance
“…The FA profile of the tropical forage utilised in this experiment differs greatly from results seen for temperate forages. Chilliard et al (2001) reported that temperate forages have 55-65% of their FA composed of linolenic acid, which was also observed in the work of Costa et al (2019) using ryegrass (Lolium perenne). The speargrass hay in the current experiment had a much lower (4% of total FA) proportion of linolenic acid than reported in temperate pastures.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The FA profile of the tropical forage utilised in this experiment differs greatly from results seen for temperate forages. Chilliard et al (2001) reported that temperate forages have 55-65% of their FA composed of linolenic acid, which was also observed in the work of Costa et al (2019) using ryegrass (Lolium perenne). The speargrass hay in the current experiment had a much lower (4% of total FA) proportion of linolenic acid than reported in temperate pastures.…”
Section: Discussionsupporting
confidence: 58%
“…Total lipid content was determined according to the method of Hara and Radin (1978). The FA content in hay, supplements, and RF was determined using a method based on Kramer et al (1997) using modifications proposed by Sun and Gibbs (2012), which was described in full by Costa et al (2019).…”
Section: Sample Collection and Analytical Proceduresmentioning
confidence: 99%
“…Indeed, Meat and Livestock Australia [ 21 ] actually describes Bos indicus as tropical breed cattle genetically adapted to survive and produce under adverse conditions, including heat and poor-quality pastures. Unique evolutionary traits of Bos indicus breeds, also known as zebu, to tropical climates are well-documented and include resistance to some ecto- and endoparasites and endemic diseases, heat and drought tolerance and other harsh environmental conditions, such as limited water, poor pasture and high humidity [ 16 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Although adapted to the local environments, Bos indicus cattle are often poor milk and meat producers [ 31 ].…”
Section: Cattle Production In the Tropicsmentioning
confidence: 99%
“…The season in the year, e.g., wet or dry, was shown to affect rumen function in grazing cattle more than forage type [ 46 ]. The animals in the current study were grazing Marandu palisade grass pastures in the wet-dry transition period.…”
Section: Discussionmentioning
confidence: 99%